Successful treatment of multidrug-resistant Acinetobacter baumanii ventriculitis with intravenous and intraventricular colistin - (:unkn) unknown (MANEY PUBLISHING, 2009)
Management of multidrug-resistant Acinetobacter baumannii (MDRAB) meningitis/ventriculitis is a difficult therapeutic problem owing to the limited penetration of antibiotics into cerebrospinal fluid (CSF). A 2-month-old girl with ventriculitis caused by MDRAB is reported. Despite therapy with intravenous (IV) colistin ventricular fluid, cultures remained positive for MDRAB. Institution of combination therapy with IV and intraventricular colistin resulted in a successful clinical and microbiological outcome. Intraventricular/intrathecal and IV colistin might be the best therapeutic option in the treatment of central nervous system infection caused by MDRAB. Further studies are required to evaluate pharmacokinetic and pharmacodynamic parameters of combined IV and intraventricular/intrathecal colistin administration, especially in children.
Keywords: GRAM-NEGATIVE BACTERIA; INTRATHECAL COLISTIN; PSEUDOMONAS-AERUGINOSA; SULFOMETHATE SODIUM; MENINGITIS; INFECTIONS; THERAPY; MANAGEMENT